2021
DOI: 10.22271/fish.2021.v9.i2c.2450
|View full text |Cite
|
Sign up to set email alerts
|

Assessing labour mobility in marine fishing operations in Karnataka

Abstract: Mobility of labour across the country continues as a major source of labour supply in ensuring economic development across all sectors including the primary sector. The migrant labour in search of better employment emancipates better living conditions through meaningful employment and better financial status. The coastal states of Maharashtra with commendable marine fish landings provides states with commendable marine fish landings provide ample opportunities for migrant fishing labour across the year. The mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…The income status of the respondents was also analysed, which indicated that about 96% of the migrants had monthly earnings between ₹10,000 to ₹20,000, whereas 3.4% of the respondents earned above ₹20,000 and about 0.7% of the migrants earned below ₹10,000 per month (Table 1). Shyam et al (2021b) in their study in Karnataka, reported that 67% of the respondents have income range of ₹20,000 to 30,000 followed by 23% having income less than ₹20,000.…”
Section: Socio-economic Characteristicsmentioning
confidence: 96%
See 2 more Smart Citations
“…The income status of the respondents was also analysed, which indicated that about 96% of the migrants had monthly earnings between ₹10,000 to ₹20,000, whereas 3.4% of the respondents earned above ₹20,000 and about 0.7% of the migrants earned below ₹10,000 per month (Table 1). Shyam et al (2021b) in their study in Karnataka, reported that 67% of the respondents have income range of ₹20,000 to 30,000 followed by 23% having income less than ₹20,000.…”
Section: Socio-economic Characteristicsmentioning
confidence: 96%
“…It can be noted that 80% of the head of the families were found illiterate and a 12% were having upper primary education (Table 1). In a study among the migrants in Karnataka, Shyam et al (2021b) revealed that 52% had completed high school, with 28% having completed secondary school level education.…”
Section: Socio-economic Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation